2016
DOI: 10.1093/humrep/dew181
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced oocyte mitochondrial defects are partially prevented and rescued by supplementation with co-enzyme Q10 in a mouse model

Abstract: This study is not a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 27 publications
4
61
0
Order By: Relevance
“…The main effect of the OreR nuclear genome to disrupt oogenesis, but not larval development, is consistent with the known tissue-specific characteristics of other metabolic dysfunctions in development and disease, and the sensitivity of oogenesis to metabolic stress, including that caused by mitochondrial dysfunction (Benkhalifa et al, 2014;Bentov et al, 2011;Boots et al, 2016;Grindler and Moley, 2013;McCall, 2004;Morrison and Spradling, 2008;Sieber et al, 2016). Although our rescue experiments showed that the allelic incompatibility between the Aatm V allele and simw 501 mitochondria causes the maternal effect embryonic lethality, preliminary observations suggest that the ovarian failure phenotype is multigenic and not just determined by alleles of Aatm.…”
Section: Discussionsupporting
confidence: 77%
“…The main effect of the OreR nuclear genome to disrupt oogenesis, but not larval development, is consistent with the known tissue-specific characteristics of other metabolic dysfunctions in development and disease, and the sensitivity of oogenesis to metabolic stress, including that caused by mitochondrial dysfunction (Benkhalifa et al, 2014;Bentov et al, 2011;Boots et al, 2016;Grindler and Moley, 2013;McCall, 2004;Morrison and Spradling, 2008;Sieber et al, 2016). Although our rescue experiments showed that the allelic incompatibility between the Aatm V allele and simw 501 mitochondria causes the maternal effect embryonic lethality, preliminary observations suggest that the ovarian failure phenotype is multigenic and not just determined by alleles of Aatm.…”
Section: Discussionsupporting
confidence: 77%
“…In the reproductive system, ROS are mainly generated within the follicle and ovulation also produces ROS . Localization of mitochondria inside the oocyte is also associated with its developmental competence …”
Section: Introductionmentioning
confidence: 99%
“…It is proved that microtubule defect can result in meiotic nondisjunction in oocytes. Several studies indicate that aberrant spindle assemble and chromosome misalignment participate in impairing the female reproduction ability in various species . Also, disrupted spindle assembly and misaligned chromosomes are supposed to be related to producing aneuploidy oocytes, which are important during infertility .…”
Section: Discussionmentioning
confidence: 99%